Implementasi Teori Belajar Humanistik dalam Pembelajaran Berdiferensiasi IPAS di Sekolah Dasar - Arzfi, Bima Prakarsa; Jamna, Jamaris (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
This research aims to analyze the application of humanistic learning theory in differentiated science learning for grade 5 phase C in elementary schools. Humanistic learning theory and differentiated science learning have similarities in understanding the importance of respecting the human side in order to suit individual characteristics. The research was conducted using a qualitative descriptive method through case studies. Research involves observing the planning, implementation and evaluation of science differentiated learning. Data is collected through diagnostic tests, observation, performance and final tests. The research subjects were 25 grade 5 students at SD Negeri 33 Sawahan for the 2023/2024 academic year. The research results show that the application of humanistic learning theory in differentiated science learning has a positive impact on student creativity and learning achievement. This can be seen from the increase in the average student creativity score from 60.69 to 87.21. Apart from that, this learning also increases student learning outcomes from an initial score of 75.45 to 88.86. The results of the research show that the application of differentiated science and science learning with humanistic learning theory can increase student creativity and learning outcomes.